2004
DOI: 10.1139/v04-059
|View full text |Cite
|
Sign up to set email alerts
|

Is acyl migration to the aglycon avoidable in 2-acyl assisted glycosylation reactions?

Abstract: This report unequivocally separates orthoester formation from acyl transfer for the first time and indicates possible routes to eliminate 2-O-acyl transfer during glycosylation reactions. Experimental evidence is shown that acyl transfer from 2-O-acyl-3,4,6-tri-O-benzyl-D-galactopyranose-derived glycosyl donors decreases in the order formyl > acetyl > pivaloyl. The 2-O-benzoyl derivatives are more variable, in some cases transferring easily, and in others not at all. Density functional theory (DFT) calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…It is well known that the use of C-2 benzoyl esters will suppress ortho-ester formation, however, this protecting group is not compatible with glycopeptide synthesis because the rather strong basic conditions required for its removal47 will result in β-elimination of the O -glycopeptide linkage. It has been shown that a 2,5-di-fluoro-benzoyl esters (dFBz) is an efficient neighboring group participant that suppresses ortho-ester formation 48,49.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the use of C-2 benzoyl esters will suppress ortho-ester formation, however, this protecting group is not compatible with glycopeptide synthesis because the rather strong basic conditions required for its removal47 will result in β-elimination of the O -glycopeptide linkage. It has been shown that a 2,5-di-fluoro-benzoyl esters (dFBz) is an efficient neighboring group participant that suppresses ortho-ester formation 48,49.…”
Section: Resultsmentioning
confidence: 99%
“…9 Our previous studies of the neighboring group-assisted glycosylation reactions, by quantum chemistry calculations, revealed that, in some cases, the relative energies of pyranose conformations determine the transition states between crucial steps. 10,11 Our previous studies also suggest that chemical modification of the rigidity of the pyranose ring controls the stereochemistry and determines the product distribution. 10,12,13 Our present goal is the complete characterization of the conformational potential energy surface of pyranoses.…”
Section: Introductionmentioning
confidence: 96%
“…23 Besides, according to our own results, other 2-hydroxy-2 0 -pivaloyloxy-1,1 0 -binaphthyl derivatives without a halide group, such as 6-nitro-2-hydroxy-2 0 -pivaloyloxy-1,1 0 -binaphthyl, 14 do not undergo isomerisation in the presence of a palladium catalyst under similar conditions.…”
Section: Resultsmentioning
confidence: 56%